Transitions of Care in Mental Health - Bueno, Denise; Detanico, Larissa Gallo; Von Diemen, Tatiana; dos Santos, Carine Líbio; Francesconi, Lenise Petter; Ceresér, Keila (Clinical and Biomedical Research, 2021)
Introduction: The occurrence of mental disorders and chronic diseases is associated with low treatment compliance and an increased mortality. The main objective of this study was to analyze medication prescriptions at hospital discharge in order to verify the patients’ access to the prescribed treatment. Methods: This is a descriptive and retrospective study performed between September 2013 and September 2018 with patients admitted in the psychiatric ward of a university hospital in the state of Rio Grande do Sul. The studied patients consisted of 274 adults over 18 years of age admitted to this hospital with at least one psychiatric comorbidity included in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) who lived in the city of Porto Alegre used specially controlled drugs, and had been hospitalized for at least 7 days. Results: Out of the 274 patients, 68.5% were readmitted once, 17.5% were readmitted twice, 9.5% were readmitted 3times, and 4.5% went through this process 4 times or more. A significant association (p = 0.014) was observed between the number of drugs not included in the Municipal Essential Medicines List upon first readmission and the number of readmissions. Among patients who were readmitted 3 times or more, 79% were prescribed drugs that were not on this list. Conclusions: The understanding of how therapeutic itineraries are established when searching for drugs contributes to setting effective lines of care where professionals may position themselves more proactively to reduce mental health complications.